High Spatio-Temporal Resolution Condenser-Free Quantitative Phase Contrast Microscopy - Ma, Ying; Ma, Lin; Zheng, Juanjuan; Liu, Min; Zalevsky, Zeev; Gao, Peng (Frontiers in Physics, 2022)
Quantitative phase-contrast microscopy (QPCM) provides an effective approach for label-free detection of transparent samples. In this study, we propose a condenser-free quantitative phase-contrast microscopy (CF-QPCM), in which several light-emitting diodes (LEDs) distributed on a ring are used for direct ultra-oblique illumination. Such condenser-free design greatly simplifies the system’s structure and releases the space for installing samples. Quantitative phase maps are reconstructed by retarding the unscattered components of the object waves for a series of phases 0, /2, , and 3/2 through a high-speed spatial light modulator (SLM). With this system, quantitative phase imaging of live cells has been achieved at a spatial resolution of 231 nm (lateral) and a frame rate of 250 Hz. We believe that the proposed CF-QPCM can contribute to biomedical, industrial, chemistry fields, etc.